If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x-22=-2(x-7)
We move all terms to the left:
-6x-22-(-2(x-7))=0
We calculate terms in parentheses: -(-2(x-7)), so:We get rid of parentheses
-2(x-7)
We multiply parentheses
-2x+14
Back to the equation:
-(-2x+14)
-6x+2x-14-22=0
We add all the numbers together, and all the variables
-4x-36=0
We move all terms containing x to the left, all other terms to the right
-4x=36
x=36/-4
x=-9
| 2|2x-5|-10=24 | | -3x+8=x-3+6-1/2(2x-4) | | 4-x-3=7 | | 11y+10=9y+32 | | 9r=-10+7r | | 0.4(10)^x=40 | | -32=x/3 | | 4d=d+21 | | 16x-50=11x+35 | | -11p+1=-8p-3p | | -7(f-8=-11 | | x/22=9=12 | | 9x+5=11x+13 | | 37.02=7g+3.98 | | 2h+7=25 | | −5r−1=−1 | | -4x=-4x+7 | | -5+6a-2-4=4a+5 | | -6-6f=3-7f | | 9x-17=x+15 | | 6x+2=2+10 | | 12+20/x=20 | | 9+5a=2a | | 7/8w=3/8 | | 5-m=-9+7+6m | | 4-n=4-7n-3n | | 201=96-w | | x–(–4)=20 | | x-2+x+x+2=72 | | -2+7u=4+4u | | 2.7z-3.5z=6 | | 2x+7x=-45 |